Effect of vildagliptin add-on treatment to metformin on plasma asymmetric dimethylarginine in type 2 diabetes mellitus patients - Cakirca, MUSTAFA; ÇAKIRCA, MUSTAFA; Soysal, Pinar; KARATOPRAK, CUMALİ; Zorlu, MEHMET; ZORLU, MEHMET; Kiskac, MUHARREM; KISKAÇ, MUHARREM; Kanat, Mustafa; CIKRIKCIOGLU, Mehmet Ali; Karatoprak, CUMALİ; SOYSAL, PINAR; et al. (My University, 2014)
Aims: A close association has been demonstrated between increased cardiovascular risk and high asymmetric dimethylarginine (ADMA) levels in type 2 diabetes mellitus (DM) patients. We planned to measure serum ADMA levels in type 2 DM patients using vildagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor. Materials and methods: A total of 68 type 2 DM patients who were on metformin were enrolled in the study. Based on the glycemic levels of patients, vildagliptin was added on to treatment in 33 patients. Patients were followed for 6 months. Serum ADMA, C-reactive protein, and fibrinogen levels were compared in groups of patients using metformin or metformin + vildagliptin, after 6 months. Results: Serum ADMA levels were found to be significantly lower in the group using vildagliptin compared to the group using metformin + vildagliptin (P<0.001). However, serum C-reactive protein and fibrinogen levels were statistically similar in the two study groups (P=0.34 and P=0.23, respectively). Conclusion: Metformin + vildagliptin treatment was observed to lower serum ADMA levels in type 2 DM patients. Our findings notwithstanding, large-scale prospective randomized controlled studies are warranted to conclude that vildagliptin provides cardiovascular protection along with diabetes regulation. Keywords: asymmetric dimethylarginine (ADMA); dipeptidyl peptidase-4 (DPP-4) inhibitor; type 2 diabetes mellitus; vildagliptin.
Keywords: type 2 diabetes